2022
DOI: 10.1136/svn-2022-001589
|View full text |Cite
|
Sign up to set email alerts
|

Association of fluid-attenuated inversion recovery vascular hyperintensity with ischaemic events in internal carotid artery or middle cerebral artery occlusion

Abstract: Background and purposeIndividuals with intracranial artery occlusion have high rates of ischaemic events and recurrence. It has been challenging to identify patients who had high-risk stroke using a simple, valid and non-invasive screening approach. This study aimed to investigate whether fluid-attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH), a specific imaging sign on the FLAIR sequence, could be a predictor of ischaemic events in a population with internal carotid artery (ICA) or middle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…exposure to teratogens such as narcotic substances, medications drugs (e.g., warfarin), or alcohol; viral infection, especially congenital cytomegalovirus infection; intrauterine fetal stroke, hypothesis supported by the frequent localization in the region of the lateral sulcus, corresponding to the vascularization area of the middle cerebral artery [13][14][15][16][17][18] ; maternal factors, such as young age (< 20 years), trauma, attempted abortion, invasive procedures for prenatal diagnosis, and lack of prenatal care. Schizencephaly is frequently described in abandoned or adopted children.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…exposure to teratogens such as narcotic substances, medications drugs (e.g., warfarin), or alcohol; viral infection, especially congenital cytomegalovirus infection; intrauterine fetal stroke, hypothesis supported by the frequent localization in the region of the lateral sulcus, corresponding to the vascularization area of the middle cerebral artery [13][14][15][16][17][18] ; maternal factors, such as young age (< 20 years), trauma, attempted abortion, invasive procedures for prenatal diagnosis, and lack of prenatal care. Schizencephaly is frequently described in abandoned or adopted children.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…intrauterine fetal stroke, hypothesis supported by the frequent localization in the region of the lateral sulcus, corresponding to the vascularization area of the middle cerebral artery 13 14 15 16 17 18 ;…”
Section: Etiopathogenesismentioning
confidence: 99%
“…FVH could serve as an objective basis for the formation of leptomeningeal collateral circulation after stroke [ 9 ]. Many studies have confirmed that FVH was correlated with circulation as well as the severity of hemodynamic impairments, opening up a new idea of exploring noninvasive assessment of the status of intracranial collaterals and prognosis [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%